Filsafat Agama - Zainul Maarif (Gerakan Indonesia Kita, 2021)
This is an effort to discuss religion philosophically. It tries to ask the very essence of religion, and then criticizes it. It says that the essence of religion is sacred, belief, teaching and promise, which is hold by human being, personally or socially. It criticizes the content of religion. It signifies religion’s sacred as a cultural product and religion’s teaching as ethics. It recommends religion’s belief begins from thinking, and anticipates religion’s promises become an absolute truth claim.